Nocturnal Experiments on Worthless Bodies: Gothic Poetics in Friedrich Engels’ Ethnography of Night Work - Althofer, Jayson (Ethnologies, 2022)
Friedrich Engels’ The Condition of the Working-Class in England (1845) features a pioneering multisensory ethnography of the factory system. His critique of the industrial revolutionization of light for 24/7 production adapted a contemporaneous Gothic imaginary of the night. In The Philosophy of Manufactures (1835), Andrew Ure repudiated a physician who condemned night-work’s effects on factory children – “if light is excluded from tadpoles, they never become frogs” – by counter-claiming: “the number and brilliancy of the gas-lights in a cotton-mill” militated against child-labourers lingering “in the tadpole state.” Dispelling Ure’s thinking as blinding fantasy, Engels revealed “the vampire property-holding class” penetrating night-workers with “very powerful light … most injurious to the sight.” He brilliantly anticipated Karl Marx’s demonstration in Capital (1867) that industrial revolutionism, involving capital’s rapid take-up of new lighting technologies, occurred “at the expense of the workpeople. Experimenta in corpore vili, like those of anatomists on frogs, were formally made.”